Calcium Phosphate Formation on Ti-Ag Alloys in Simulated Body Fluid - Masatoshi TAKAHASHI; Masafumi KIKUCHI; Kouki HATORI; Yusuke ORII; Keiichi SASAKI; Yukyo TAKADA (Journal of Biomechanical Science and Engineering, 2009)
Ti-Ag alloys with 20 and 25 mass% Ag were prepared; their surfaces were polished using silicon carbide abrasive papers. The polished alloys were immersed in a simulated body fluid (SBF), and their surfaces were observed by scanning electron microscope (SEM) to investigate the spontaneous formation of calcium phosphates. The precipitates formed on the alloys were qualitatively and quantitatively analyzed using an electron probe microanalyzer (EPMA), with pure titanium and silver used as controls. Hardness and surface roughness, which was measured as the height parameter Ra, were examined, and their effect on calcium phosphate formation was elucidated. On immersion in SBF, calcium phosphates were formed on the Ti-Ag alloys and pure titanium but not on pure silver. The amount of the precipitate and the concentration ratios of calcium to phosphorus in the precipitates of the Ti-Ag alloys and pure titanium did not differ significantly. The Ti-Ag alloys showed significantly higher hardness and lower Ra values than pure titanium. The Ra values of the metals decreased as their hardness increased. The Ra values of the metals appeared to have very little effect on calcium phosphate formation. The results of this study have verified the biocompatibility of the Ti-Ag alloys, making them suitable for use as dental and orthopedic implants.